Iconography of the White Old Man — Tsagaan Ebugen’s Image in Mongolian Ethnic Art - Batchuluun, Sergelen (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2021)
This article attempts to compare written primary sources, such as sutras dedicated to Tsagaan Ebugen, with a range of different visual materials, and take into consideration the unity of cultural and artistic aspects. Based on different art materials collected by the author including fifty-four Mongolian, eighteen Kalmyk, and twenty-one Buryat images, the author shows the features and aspects of the iconography of the image based on the details of clothing. The article provides a detailed analysis of the whole complex of iconographic elements included in the image of Tsagaan Ebugen, such as face, hair, figure, clothes, shoes, and hats. The purpose of the article is to present the results of the analysis of art materials associated with the image of the White Old Man as well as to identify the most stable and persistent iconographic features of the image. The pictorial iconography of Tsagaan Ebugen reflects the complex relationship between the ancient chthonic and Buddhist principles. As a result of the study, it is demonstated that traditional elements of clothing are preserved in the image of the lord of the earth and water of the White Old Man, and only ten percent of all images collected by the author are an exception and have other elements of clothing details that appeared due to the historical and religious influence in the region.